ANALISIS PENGARUH KEPEMILIKAN SAHAM BESAR BERGANDA DAN AKTIFITAS KOMITE AUDIT TERHADAP AUDIT FEE - Dilla Fadilla, Muhammmad; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2019)
In order to achieve the best reporting quality, shareholders may choose the best public accountant firm to audit the company. Using 177 companies (observations of 364 annual financial statements of non-financial and non-utility companies) as samples, the purpose of this study is to examine whether audit costs are influenced by several factors such as multiple large shareholders and audit committee activities. This study uses Total Assets, Total Receivables divided by Total Assets, Audit Experience, Chartered Audit, Holding by Shareholders, Net Loss in the Period, Number of Employees, and Audit Committee Size as control variables.This study uses secondary data from the financial statements of non-financial and non-utility companies listed on the Indonesia Stock Exchange in 2016. The method used for this study was purposive sampling.The results of this study indicate that all hypotheses are accepted. This is because multiple large shareholders and audit committee activities positively and significantly affect audit fees.